2014
DOI: 10.1021/mp500286b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inter- and Intramolecular Interactions on the Physical Stability of Indomethacin Dispersed in Acetylated Saccharides

Abstract: Differential scanning calorimetry (DSC), broadband dielectric (BDS), and Fourier transform infrared (FTIR) spectroscopies as well as theoretical computations were applied to investigate inter- and intramolecular interactions between the active pharmaceutical ingredient (API) indomethacin (IMC) and a series of acetylated saccharides. It was found that solid dispersions formed by modified glucose and IMC are the least physically stable of all studied samples. Dielectric measurements showed that this finding is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 52 publications
(78 reference statements)
2
29
0
Order By: Relevance
“…IR and Raman spectroscopy are also important tools to study changes in intermolecular interactions upon amorphization and the presence of drug-polymer or drugcoformer interactions that stabilize the system [202][203][204][205][206][207][208]287]. H bonding between the drug and the polymer or coformer can affect the molecular mobility of the API, inhibit H bonding between two API molecules and can impact on the crystallization driving force due to the relative strength of API-polymer/coformer and API-API H bonds.…”
Section: Savolainen Et Al Reported An Example Where In Situmentioning
confidence: 99%
“…IR and Raman spectroscopy are also important tools to study changes in intermolecular interactions upon amorphization and the presence of drug-polymer or drugcoformer interactions that stabilize the system [202][203][204][205][206][207][208]287]. H bonding between the drug and the polymer or coformer can affect the molecular mobility of the API, inhibit H bonding between two API molecules and can impact on the crystallization driving force due to the relative strength of API-polymer/coformer and API-API H bonds.…”
Section: Savolainen Et Al Reported An Example Where In Situmentioning
confidence: 99%
“…[21][22] Studies have shown that small molecules like amino acids, sugar, urea, citric acid, kaolin, aluminium hydroxide 23 or other API can improve physical stability of the amorphous drugs more effectively than polymers. [24][25][26] The main reason for the stability of the co-amorphous system was attributed to molecular interactions between the drugs/excipient in the system. It was reported that unstable drug like Naproxen could be stabilized by Indomethacin and Cimetidine, and dissolution rates of these systems were also enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Acetylated starch is classified by the Food and Drug Administration (FDA) as a Generally Recognized as Safe (GRAS) material. Numerous investigations regarding the use of various sugar derivatives, i.e., acetylated sucrose, glucose, maltose, galactose, to stabilize amorphous forms of drugs, such as indomethacin, itraconazole, and nifedipine have been published (6,17,18). Solid dispersions composed of amorphous APIs have been obtained by melting with appropriate ratios of active substances and modified saccharides followed by rapid cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been found that the amorphous form of API remained stable even after 1 year of storage under room conditions (22). In this context, application of acetylated saccharides in the formulation seems to be a promising option (11,17,18).…”
Section: Introductionmentioning
confidence: 99%